EVALUATION OF CONCEPT OF ANTIMICROBIAL STEWARDSHIP AMONG UG MEDICAL STUDENTS FOR BETTER UNDERSTANDING OF USE OF ANTIMICROBIAL AGENTS AND MINIMIZING ANTIMICROBIAL RESISTANCE - JYOTI S PATIL; PRIYA P VISHWAKARMA; ANAND M INGALE; RASHMI M KARIGOUDAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of this study is to assess interns perception and knowledge about antibiotic stewardship and their preparedness for appropriate use of antimicrobials and to prescribe antimicrobials. Methods: The 164 medical interns of BLDE (DU)’s Shri B.M. Patil Medical College who provided consent to participate in the study were included in this cross-sectional web-based online survey. The study was carried out using a validated questionnaire. The data were analyzed using the statistical tool for the social sciences (Version 20). Results: Out of the 164 interns, 133 (83.1%) completed the entire survey. The term “antimicrobial stewardship” was familiar to 51% (n=68). 50% (n=66) agreed that antibiotics are inappropriately used at the hospital. Approximately 88% (n=104) and 85% (n=113) of the interns thought that insufficient infection control practices and the use of wide spectrum antibiotics were the main causes of resistance development, respectively. About 90% (n=119) thought that lecture series and grand round discussions on the responsible use of antibiotics were good educational tools. About 37% (n=49), 41% (n=54), and 24% (n=32) of the interns understood the proper antibiotic selection for treating simple cases of urinary tract infections, could de-escalate antibiotic therapy, understand an anti-biogram, and could match a different combination of antimicrobials and microorganisms, respectively. Conclusion: The major findings of our study were, despite students having good perception, the knowledge component was inadequate, that is, they lacked their preparedness and confidence to prescribe antibiotics which emphasizes that the students are aware of the antimicrobial stewardship but their knowledge domain needs to be improved for better application in their clinical practice.